PENGGUNAAN KATA KERJA PADA NOVEL SURGA YANG TAK DI RINDUKAN KARYA ASMA NADIA - Dewi Sartika; Margoreta Dea; Febriati Imel; Saptiana Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The article entitled “The Use of Verbs in the Novel Surga yang Tak Dirindukan by Asma Nadia” aims to describe the forms, functions, and usage of verbs in constructing sentence structures within the novel. This study focuses on the analysis of basic verbs and derived verbs found in narrative texts and character dialogues. The research employs a qualitative descriptive method with data collection techniques involving observation and note-taking, while data analysis is conducted using a syntactic approach. The data source of this research is the novel Surga yang Tak Dirindukan by Asma Nadia as a representation of language use in popular literary works. The findings reveal that the dominant types of verbs used are active verbs, both transitive and intransitive, which function as the main predicates in sentences. Furthermore, various affixation patterns were identified, influencing grammatical meanings and enriching narrative expressions. The use of verbs also plays an important role in portraying plot dynamics and character emotions. This study concludes that verbs have a central role in constructing meaning and sentence structures in the novel.